Expression Kinetics and Innate Immune Response after Electroporation and LNP-Mediated Delivery of a Self-Amplifying mRNA in the Skin - Hanne Huysmans; Zifu Zhong; Joyca De Temmerman; Barbara L. Mui; Ying K. Tam; Séan Mc Cafferty; Arlieke Gitsels; Daisy Vanrompay; Niek N. Sanders (Elsevier, 2019)
In this work, we studied the expression kinetics and innate immune response of a self-amplifying mRNA (sa-RNA) after electroporation and lipid-nanoparticle (LNP)-mediated delivery in the skin of mice. Intradermal electroporation of the sa-RNA resulted in a plateau-shaped expression, with the plateau between day 3 and day 10. The overall protein expression of sa-RNA was significantly higher than that obtained after electroporation of plasmid DNA (pDNA) or non-replication mRNAs. Moreover, using IFN-β reporter mice, we elucidated that intradermal electroporation of sa-RNA induced a short-lived moderate innate immune response, which did not affect the expression of the sa-RNA. A completely different expression profile and innate immune response were observed when LNPs were used. The expression peaked 24 h after intradermal injection of sa-RNA-LNPs and subsequently showed a sharp drop. This drop might be explained by a translational blockage caused by the strong innate immune response that we observed in IFN-β reporter mice shortly (4 h) after intradermal injection of sa-RNA-LNPs. A final interesting observation was the capacity of sa-RNA-LNPs to transfect the draining lymph nodes after intradermal injection. Keywords: self-amplifying mRNA, pDNA, non-replicating mRNA, lipid nanoparticles, innate immune response, electroporation, intradermal, expression kinetics, mice